Information Support for Health Saving of Adults - Musin, Oleg A. (2020)
This article deals with the formation of cognitive interest in leading a healthy lifestyle through information portals of the Internet environment. In addition, the results of research related to the inclusion of adults in the health environment are presented. The purpose of the article is to define the content of the information portal, which would meet the needs and requirements of adult users. The work used methods of analysis and synthesis of scientific and methodological literature and information environment on health improvement, methods of mathematical statistics. Publications in periodicals, methodological materials, monographs and information portals related to healthy lifestyle were used as sources of information. The article presents the results of a survey of adults, which made it possible to define the criteria and content of the information portal on healthy lifestyle. Based on the needs of users, the requirements that should be considered when designing such information portals were identified. The results will be useful for specialists developing information content portals aimed at supporting healthy lifestyle, as well as adults who are subjects of self-development, to lead a healthy life with the support of the information environment. Identified relevant content will be the basis for expanding the idea of what the information space related to healthy lifestyle should look like, as well as help self-development actors to design an individual set of health-forming practices.